1992
DOI: 10.2331/suisan.58.2101
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Ascorbyl-2-Phosphate to Ascorbic Acid in Rainbow Trout.

Abstract: Conversion of L-ascorbyl-2-phosphate (ASP) to L-ascorbic acid (AsA) was investigated in vivo in rainbow trout Oncorhynchus mykiss administered with AsP orally and intraperitoneally. AsP magnesium salt or AsA (each 200ƒÊmol in 2g of casein basal diet) was orally administered to each rainbow trout once. The fish were sacrificed at varying intervals during the experimental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…It is conceivable that all the AsP transported in such a form is readily hydrolyzed to AsA in the body, because AsP has an equivalent physiologi cal activity to that of AsA 5) and the liver had a high activity of AsP hydrolysis in this investigation. The present in vitro findings support the results of our previous in vivo investigations 5,7) showing the ready conversion of AsP to AsA in the rainbow trout body. DNP is one of the uncouplers that inhibit ATP synthesis.…”
Section: Procedures For Absorption Testsupporting
confidence: 82%
See 1 more Smart Citation
“…It is conceivable that all the AsP transported in such a form is readily hydrolyzed to AsA in the body, because AsP has an equivalent physiologi cal activity to that of AsA 5) and the liver had a high activity of AsP hydrolysis in this investigation. The present in vitro findings support the results of our previous in vivo investigations 5,7) showing the ready conversion of AsP to AsA in the rainbow trout body. DNP is one of the uncouplers that inhibit ATP synthesis.…”
Section: Procedures For Absorption Testsupporting
confidence: 82%
“…The HPLC conditions have been reported previously, 7) with the exception of the UV detector. The detector used was the Hitachi L-4000 UV detector, set at 254 nm.…”
Section: Reagentsmentioning
confidence: 99%
“…Thus, an exogenous source of AA is required in fish diets. Many studies reported the positive effects of AA on growth performances of fish [5][6][7][8][9][10]. On the other hand, there were some contradictory reports that dietary AA did not improve the growth performance of seabream [3] and yellow croaker [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have focused on finding more stable and bioavailable forms of AA to replace L‐ascorbic acid, which is the thermolabile, unstable vitamin C. Phosphate derivatives of AA have been shown to have antiscorbutic activity in channel catfish, Ictalurus punctatus (Rafinesque) (Wilson, Poe & Robinson 1989; El Naggar & Lovell 1991a,b); tilapia, Oreochromis niloticus (Steindachner) (Soliman, Jauncey & Roberts 1986; Shiau & Hsu 1995); rainbow trout, Oncorhynchus mykiss (Walbaum) (Miyasaki, Sato, Yoshinaka & Sakaguchi 1992; Cho & Cowey 1993); Japanese yellowtail, Seriola quinqueradiata (Temminck et Schlegel) (Kanazawa, Teshima, Koshio, Higashi & Itoh 1992); Kuman shrimp, Penaeus japonicus (Bate) (Shigueno & Itoh 1988) and grass shrimp, Penaeus monodon (Fabricius) (Shiau & Hsu 1994). Matusiewicz & Dabrowski (1995) concluded that fish (rainbow trout) have the ability to utilize ascorbic phosphate derivatives.…”
Section: Introductionmentioning
confidence: 99%